Investigating the effect of hole size, bottom hole temperature, and composition on cement bonding quality of exploratory wells in Iran - Pooria Kianoush; Farough Mesgari; Emad Jamshidi; Mostafa Gomar; Ali Kadkhodaie; Shahab Varkouhi (Scientific Reports)
Abstract The oil and gas industry’s reliance on well cementing practices to ensure well integrity and productivity is a pressing concern, particularly in exploratory wells where unpredictable conditions can lead to subpar cement bonding efficiency. This study addresses the pressing issue of optimizing cementing practices in Iran’s exploratory wells, ensuring better well integrity and productivity. The preliminary objective is to investigate the impact of hole size and bottom hole temperature variations on cement bonding efficiency in these wells. We analyzed cement quality logs from 21 exploratory wells in reservoir zones between 2012 and 2022 to achieve this. The study employed a systematic approach, using CBL/VDL and cement formulation to assess the quality of each wellbore section separately. We designed a cement formulation based on changes in bottom hole temperature and gas migration control and implemented it using three different contractors, each with unique additives. It allowed us to compare the quality of cement resulting from different phases and additives. Our results show that cement designed with dominant liquid additions in the 5-inch liner phase exhibits better bonding than formulations with increased powder form additives, specifically those containing a liquid dispersant, liquid fluid loss controller, liquid anti-gas migration, and liquid H.T. retarder for LNR 5 inch. Additionally, smaller hole sizes demonstrate better cement bonding quality due to reduced fluid flow and less turbulence. These findings have significant implications for optimizing cementing practices in the petroleum industry, particularly in Iran’s exploratory wells. Overall, this investigation provides valuable insights for improving wellbore integrity and productivity by optimizing cementing practices, which can be applied to future drilling operations in Iran’s exploratory wells.